THE RELATIONSHIP BETWEEN ORGANIZATIONAL JUSTICE AND EMPLOYEE SILENCE: A STUDY ON PUBLIC EMPLOYEES - Yavuz, Ayşe (Horizons - International Scientific Journal, 2022)
Even though technological developments continue to be experienced at a dizzying pace in today’s business world, the human factor continues to maintain its importance. For this reason, many managerial issues continue to emerge. The concept of organizational justice is one of these issues, which reveals the expectations of the employees from the organization in return for the effort they spend for the organization. Employees in organizations where organizational justice is provided work more happily. Employee silence, which is another concept related to the human factor, is the behavior of employees to avoid expressing their positive or negative thoughts about the organization. It is critical for the success of the organization that the employees can express their ideas clearly and easily express their suggestions and problems. It is thought that in businesses where organizational justice exists, employees can freely express their opinions and thus silence behaviors will decrease. In this study, the relationship between organizational justice and employee silence is examined. Research data were collected from public servants in a district of Konya through a survey technique. The obtained data were analyzed with statistical methods. As a result, a significant relationship was found between the concepts of organizational justice and organizational silence.